Low-temperature oxidizing plasma surface modification and composite polymer thin-film fabrication techniques for tailoring the composition and behavior of polymer surfaces - Tompkins, Brendan D., author; Fisher, Ellen R., advisor; Henry, Charles S., committee member; Bailey, Travis S., committee member; Szamel, Grzegorz, committee member; James, Susan P., committee member (Colorado State University. Libraries, 2014)
This dissertation examines methods for modifying the composition and behavior of polymer material surfaces. This is accomplished using (1) low-temperature low-density oxidizing plasmas to etch and implant new functionality on polymers, and (2) plasma enhanced chemical vapor deposition (PECVD) techniques to fabricate composite polymer materials. Emphases are placed on the structure of modified polymer surfaces, the evolution of polymer surfaces after treatment, and the species responsible for modifying polymers during plasma processing. H2O vapor plasma modification of high-density polyethylene (HDPE), low-density polyethylene (LDPE), polypropylene (PP), polystyrene (PS), polycarbonate (PC), and 75A polyurethane (PU) was examined to further our understanding of polymer surface reorganization leading to hydrophobic recovery. Water contact angles (wCA) measurements showed that PP and PS were the most susceptible to hydrophobic recovery, while PC and HDPE were the most stable. X-ray photoelectron spectroscopy (XPS) revealed a significant quantity of polar functional groups on the surface of all treated polymer samples. Shifts in the C1s binding energies (BE) with sample age were measured on PP and PS, revealing that surface reorganization was responsible for hydrophobic recovery on these materials. Differential scanning calorimetry (DSC) was used to rule out the intrinsic thermal properties as the cause of reorganization and hydrophobic recovery on HDPE, LDPE, and PP. The different contributions that polymer cross-linking and chain scission mechanisms make to polymer aging effects are considered. The H2O plasma treatment technique was extended to the modification of 0.2 µm and 3.0 µm track-etched polycarbonate (PC-TE) and track-etched polyethylene terephthalate (PET-TE) membranes with the goal of permanently increasing the hydrophilicity of the membrane surfaces. Contact angle measurements on freshly treated and aged samples confirmed the wettability of the membrane surfaces was significantly improved by plasma treatment. XPS and SEM analyses revealed increased oxygen incorporation onto the surface of the membranes, without any damage to the surface or pore structure. Contact angle measurements on a membrane treated in a stacked assembly suggest the plasma effectively modified the entire pore cross section. Plasma treatment also increased water flux through the membranes, with results from plasma modified membranes matching those from commercially available hydrophilic membranes (treated with wetting agent). Mechanisms for the observed modification are discussed in terms of OH and O radicals implanting oxygen functionality into the polymers. Oxidizing plasma systems (O2, CO2, H2O vapor, and formic acid vapor) were used to modify track-etched polycarbonate membranes and explore the mechanisms and species responsible for etching polycarbonate during plasma processing. Etch rates were measured using scanning electron microscopy; modified polycarbonate surfaces were further characterized using x-ray photoelectron spectroscopy and water contact angles. Etch rates and surface characterization results were combined with optical emission spectroscopy data used to identify gas-phase species and their relative densities. Although the oxide functionalities implanted by each plasma system were similar, the H2O vapor and formic acid vapor plasmas yielded the lowest contact angles after treatment. The CO2, H2O vapor, and formic acid vapor plasma-modified surfaces were, however, found to be similarly stable one month after treatment. Overall, etch rate correlated directly to the relative gas-phase density of atomic oxygen and, to a lesser extent, hydroxyl radicals. PECVD of acetic acid vapor (CH3COOH) was used to deposit films on PC-TE and silicon wafer substrates. The CH3COOH films were characterized using XPS, wCA, and SEM. This modification technique resulted in continuous deposition and self-limiting deposition of a-CxOyHz films on Si wafers and PC-TE, respectively. The self-limiting deposition on PC-TE revealed that resulting films have minimal impact on 3D PC structures. This technique would allow for more precise fabrication of patterned or nano-textured PC. PECVD is used to synthesize hydrocarbon/fluorocarbon thin films with compositional gradients by continuously changing the ratio of gases in a C3F8/H2 plasma. The films are characterized using variable angle spectroscopic ellipsometry (VASE), Fourier transform infrared spectroscopy (FTIR), XPS, wCA, and SEM. These methods revealed that shifting spectroscopic signals can be used to characterize organization in the deposited film. Using these methods, along with gas-phase diagnostics, film chemistry and the underlying deposition mechanisms are elucidated, leading to a model that accurately predicts film thickness.
Keywords: gradient film; track-etched membrane; polymer etching; plasma enhanced-chemical vapor deposition; plasma surface modification; fluorocarbon plasma